2022
DOI: 10.1371/journal.pone.0269847
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun proteomic profiling of dormant, ‘non-culturable’ Mycobacterium tuberculosis

Abstract: Dormant cells of Mycobacterium tuberculosis, in addition to low metabolic activity and a high level of drug resistance, are characterized by ‘non-culturability’–a specific reversible state of the inability of the cells to grow on solid media. The biochemical characterization of this physiological state of the pathogen is only superficial, pending clarification of the metabolic processes that may exist in such cells. In this study, applying LC-MS proteomic profiling, we report the analysis of proteins accumulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…In the present study, dormant forms of Mtb were obtained as a result of gradual environmental acidification in the late stationary phase (40–60 days from the moment of inoculation) under aerobic conditions 18 . Such dormant forms were characterized by morphological, biochemical and physiological changes in comparison with actively grown bacteria 18 as well as by differences on transcriptomic and proteomic level 19 , 20 . The appearance of dormant forms was monitored by the decrease in uracil incorporation in the culture, as well as the development of “non-culturability” (decrease in CFU number up to zero 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, dormant forms of Mtb were obtained as a result of gradual environmental acidification in the late stationary phase (40–60 days from the moment of inoculation) under aerobic conditions 18 . Such dormant forms were characterized by morphological, biochemical and physiological changes in comparison with actively grown bacteria 18 as well as by differences on transcriptomic and proteomic level 19 , 20 . The appearance of dormant forms was monitored by the decrease in uracil incorporation in the culture, as well as the development of “non-culturability” (decrease in CFU number up to zero 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, the MFT gene locus seems to be derepressed by long-chain fatty acid-CoA esters in M. smegmatis, which bind to the repressor mftR (10). Furthermore, a comparison of the proteome of active and dormant cells revealed that mftD (Rv0694) was upregulated in the dormant state, which is associated with the persistence of M. tuberculosis in macrophages (11). Lastly, a study on the impact of mycofactocin inactivation (∆mftD) on M. tuberculosis showed increased growth on glucose containing media as well as a decreased number of mycobacterial cells in a mouse model after the onset of hypoxia (12).…”
Section: Introductionmentioning
confidence: 99%